2017
DOI: 10.1111/pedi.12567
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving for children with type 1 diabetes and clinical outcomes in central India: The IDREAM study

Abstract: Parents of children diagnosed with T1D early in life remain involved in care throughout the child's adolescence. Parents of children diagnosed in late childhood and early adolescence are significantly less involved in care, and this is associated with worse glycemic control. Clinics must know who performs care tasks and tailor diabetes education appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…This investigation into diabetes in Jamaica has partly agreed with other research conducted in developing countries on caregivers, 6,7,14,26,27 whose primary difference from studies in developed countries is the salience of lack of access to resources 6,14,26 and cultural factors. 6,14 In this study, a salient cultural factor was participants' religiosity, as demonstrated by their dependence on religion as a coping strategy.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This investigation into diabetes in Jamaica has partly agreed with other research conducted in developing countries on caregivers, 6,7,14,26,27 whose primary difference from studies in developed countries is the salience of lack of access to resources 6,14,26 and cultural factors. 6,14 In this study, a salient cultural factor was participants' religiosity, as demonstrated by their dependence on religion as a coping strategy.…”
Section: Discussionsupporting
confidence: 80%
“…3,5,14 Poor coping involves overprotective behaviour, poor communication, distancing, and emotional instability. 8,15 In the diabetes literature, relatively few studies focus on caregivers of children with diabetes in developing countries 7 or make rural/urban comparisons. Jamaican diabetes research is predominantly quantitative: studies focus on adults and epidemiological concerns such as risk factors, prevalence, knowledge, and morbidity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 5-1619 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) <0.001* patients were aged ≥65 years; thus, they were categorized into the ≥45 years age group (Table 2). Regarding health insurance schemes, the majority of patients (67.4%) had Universal Health Coverage Scheme, 13.1% had Civil Servant Medical Benefit Scheme and 10.1% were covered by Social Security Scheme.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…In particular, school nurses recognized the significance of partnerships between schools and families. For example, in an interventional study, parental involvement in disease management, such as determining insulin dose, was associated with lower hemoglobin A1c levels among children with diabetes (Friedemann‐Sanchez et al, 2018). This is similar to another review that found school nurses provide collaboration and communication in the care coordination process for children with complex needs (McClanahan & Weismuller, 2015).…”
Section: Discussionmentioning
confidence: 99%